Civilizational imperatives Americans, Moros, and the colonial world - Charbonneau, Oliver 1984- (Quezon City, Philippines Ateneo de Manila University Press, 2021)
"This book reveals the little-known story of how the United States colonized and governed Southeast Asian Muslim territories in the early twentieth century"--Provided by publisher.
Other frontiers -- Imagining the Moro: racial and spatial fantasies in Mindanao-Sulu -- Courtrooms, clinics, and colonies: remaking the southern Philippines -- Civilizational imperatives: building colonial classrooms -- Corrective violence: on fear, massacre, and punishment -- Tropical idylls: maintaining colonial spaces and bodies -- Moros in America: visiting the metropole in fact and fiction -- Imperial interactivities: Mindanao-Sulu in a connected world -- Colonial remains.
A reprint of the same edition published by Cornell University Press.
Includes bibliographical references and index.
Keywords: Muslims -- Philippines -- History -- 20th century; Imperialism -- History -- 20th century; Philippines -- Colonization -- History -- 20th century; United States -- Foreign relations -- Philippines; Philippines -- Foreign relations -- United States